THE INFLUENCE OF VOLCANO ERUPTION EXPERIMENTS ON THE COGNITIVE DEVELOPMENT OF CHILDREN IN GROUP B1 IN TK AL- HIKMAH - Rosida; Ruqoyyah Fitri (Adisam Publisher, 2024)
This study aims to examine the impact of a volcanic eruption experiment on the cognitive development of early childhood students at TK Al-Hikmah Ketapang Banyuwangi. Using an experimental method with a One-Group Pretest-Posttest design, the sample consisted of 15 children from group B1. The results showed a significant increase in the children's cognitive abilities after the treatment. Before the treatment, most children were in the